Nilai-Nilai yang Terkandung dalam Seni Islam: Studi Pemikiran Seyyed Hossein Nasr - Farkhan Fuady; Nurisman Nurisman (El-Afkar: Jurnal Pemikiran Keislaman dan Tafsir Hadis, 2023)
The presence of Islamic art in human life is able to provide a spiritual experience. Through Islamic art, humans are able to take lessons regarding the principles of the oneness of God. Nasr believes that Islamic art is a tool to build awareness on the religious side. Therefore its presence contains meaning and values in it. This paper seeks to provide an explanation of Islamic art, especially the perspective of Seyyed Hossein Nasr. The method used is a qualitative method with this type of research. The data source is divided into two, namely the primary data source in the form of a book entitled Islamic Art and Spirituality and Knowledge and Purity. Furthermore, researchers also use secondary data that comes from various sources that discuss the research topic. The results of the research show that Nasr believes that Islamic art is the embodiment or manifestation of the oneness of Allah SWT. Islamic art also has a close relationship with Islamic spirituality. The source of Islamic art is the aspects contained in the Qur'an. While the values contained in art generally consist of two, namely intrinsic values and extrinsic values. Regarding the values contained in Islamic art according to Seyyed Hossein Nasr, there are three. These values are aesthetic values, ethical values, and spiritual values.